218 Action Potential Alternans in the Ageing Ovine Atria. (31st May 2014) - Pearman, Charles; Trafford, Andrew; Eisner, David; Dibb, Katharine
Abstract : Background: The incidence of atrial fibrillation (AF) has a steep relationship with age. AF prevalence in persons aged over 85 exceeds 15% in European cohorts. The basis for the exaggerated vulnerability of the atria to fibrillation in the elderly is incompletely understood. Previous work has shown that ageing is associated with a prolongation of action potential duration, a finding that could be expected to protect against re-entrant arrhythmias. Alternating beat to beat variation in action potential duration and amplitude occurs at high heart rates and has been associated with a history of AF in humans. We investigated whether isolated atrial myocytes from young and old sheep would exhibit differences in alternans behaviour. Methods: Myocytes from the left and right atrial appendages were isolated from young (<18 months, n = 51 cells, 20 animals) and old (>8 years, n = 51 cells, 16 animals) welsh mountain sheep. Action potentials were recorded using perforated patch clamp in current clamp mode. Myocytes were incrementally stimulated from 0.25 to 8 Hz for 80 cycles. Action potential morphology was analysed and quantification of alternans behaviour was achieved using a discrete fourier transform of action potential trains and subsequent spectral analysis. Action potential duration was assessed at 90% repolarisation (APD90). Results: Atrial myocytes from old sheep had a longer APD90 than those from young sheep (488.1 ± 29.3 ms vs. 374.3 ± 31.0 ms in LA at 0.5Hz, p < 0.05). Myocytes from the left and right atria displayed alternans of both phase 0–1 (amplitude) and phase 2–3 (repolarisation). Myocytes from older sheep exhibited alternans behaviour at lower stimulation frequencies than those from young sheep and the oscillations were of a greater magnitude (p < 0.05). Age related changes in alternans were more prominent in the right than the left atrium. Interpretation: The longer action potentials seen in atrial myocytes from aged sheep are associated with a decrease in the alternans threshold and an increase in alternans magnitude. These findings help to explain the pro-arrhythmic phenotype of senescence.